Exploring the role of reflective teaching in professional growth: insights from Vietnamese tertiary EFL educators - Pham Trut Thuy; Tran Thi Thuy; Le Thanh Thao (Erudita: Journal of English Language Teaching, 2024)
This qualitative study investigates the perceptions of Vietnamese tertiary English as a Foreign Language (EFL) teachers on the effectiveness of reflective teaching practices in their professional development. Reflective teaching is essential in continuously improving teaching methodologies and fostering a deeper understanding of instructional practices and student learning. Moreover, reflective teaching, a critical self-assessment methodology, is increasingly recognized as pivotal in adapting and enhancing teaching strategies in diverse educational environments. The study recruited nine Vietnamese tertiary EFL teachers from two institutions, representing a range of career stages: novice, mid-career, and near-end. Through semi-structured interviews, the research explored the teachers’ experiences and views on the integration, challenges, impact on professional identity, and the effects of reflective practices on student engagement and learning outcomes. Key findings revealed that reflective teaching significantly influences teaching methodologies across different career stages, with each group adapting these practices uniquely. Challenges such as time management and adapting to educational technologies were noted, along with their solutions. Reflective practices were instrumental in shaping teachers’ professional identities and enhancing student engagement and learning outcomes. The study underscores the importance of reflective practices in EFL teaching, emphasizing the need for tailored professional development programs and institutional support.